2017
DOI: 10.1128/mbio.00822-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Bacillus thuringiensis Reveals a Path to Specialized Exploitation of Multiple Invertebrate Hosts

Abstract: Understanding the genetic basis of host shifts is a key genomic question for pathogen and parasite biology. The Bacillus cereus group, which encompasses Bacillus thuringiensis and Bacillus anthracis, contains pathogens that can infect insects, nematodes, and vertebrates. Since the target range of the essential virulence factors (Cry toxins) and many isolates is well known, this group presents a powerful system for investigating how pathogens can diversify and adapt to phylogenetically distant hosts. Specializa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 77 publications
8
51
0
Order By: Relevance
“…The pXO2 plasmid of Ba was phylogenetically restricted to Ba, although plasmids with homology to pXO1 are widely distributed in clades 1 and 2 (Hu, Swiecicka, et al, 2009;Zheng et al, 2013). A large number of plasmids, including the Cry-bearing plasmids which possess orf156/157 minireplicons (Zheng et al, 2013), were phylogenetically restricted to clade 2 (Figures 4 and 5), as has been found previously (Zheng et al, 2017). Infectious cooperation, on the other hand, predicts that conjugative plasmids carrying social genes such as Cry toxins should be widely distributed across clades and show evidence of recent horizontal transfer.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The pXO2 plasmid of Ba was phylogenetically restricted to Ba, although plasmids with homology to pXO1 are widely distributed in clades 1 and 2 (Hu, Swiecicka, et al, 2009;Zheng et al, 2013). A large number of plasmids, including the Cry-bearing plasmids which possess orf156/157 minireplicons (Zheng et al, 2013), were phylogenetically restricted to clade 2 (Figures 4 and 5), as has been found previously (Zheng et al, 2017). Infectious cooperation, on the other hand, predicts that conjugative plasmids carrying social genes such as Cry toxins should be widely distributed across clades and show evidence of recent horizontal transfer.…”
Section: Discussionsupporting
confidence: 77%
“…Our genomic analysis highlights the inconsistency of Bc , Ba or Bt as species designations based upon phenotype comparisons, particularly for Bc and Bt that can share aspects of their ecology and do not represent discrete cohesive lineage clusters. However, all subsequent phylogenies of B. cereus group isolates, including this work and previous MLST studies, have shown that there are several cohesive genetically distinct clades in the B. cereus group (Cardazzo et al., ; Didelot et al., ; Guinebretière et al., ; Priest et al., ; Raymond, Wyres, et al., ; Sorokin et al., ; Vassileva et al., ; Vilas‐Boas, Sanchis, Lereclus, Lemos, & Bourguet, ; Zheng et al., ). The three major clades originally defined by MLST ( Ba and relatives—clade 1, B. kurstaki and Bc —clade 2 and B. weihenstephanensis —clade 3) were recovered in this study, although the distribution of predicted insecticidal genes and of isolates identified as B. weihenstephanensis and B. mycoides , indicates that there can be additional significant heterogeneity within these clades (Figures and ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Bacillus anthracis shares a common chromosomal framework with all main species of the Bacillus cereus ( sensu lato ) super‐species group, including the opportunistic soil bacterium B. cereus , and the entomopathogenic B. thuringiensis , which (because of analogous plasmids occurring throughout the group) sometimes leads to blurred species boundaries (Helgason et al ., ; Priest et al ., ; Kolstø, Tourasse & Økstad, ; Zwick et al ., ; Bazinet, ; Zheng et al ., ). The chromosomal elements principally separating classic B. anthracis ( senso stricto ) from the other closely related species are: (1) the presence of four distinctive chromosomal prophage elements; (2) a specific, inactivating nonsense mutation in the transcription factor PlcR, a positive regulator mainly of chromosomally encoded extracellular virulence factors that are important during mammalian and insect infections by B. cereus and B. thuringiensis ; and (3) being part of the genetically monomorphic B. anthracis cluster by phylogenetic analysis (Kolstø et al ., ).…”
Section: Anthrax: a Case Study In Slow Integrationmentioning
confidence: 99%
“…Bacillus anthracis shares a common chromosomal framework with all main species of the Bacillus cereus (sensu lato ) super-species group, including the opportunistic soil bacterium B. cereus , and the entomopathogenic B. thuringiensis , which (because of analogous plasmids occurring throughout the group) sometimes leads to blurred species boundaries. 5560 The chromosomal elements principally separating classic B. anthracis (senso stricto ) from the other closely related species are: 1) the presence of four distinctive chromosomal prophage elements; 2) a specific, inactivating nonsense mutation in the transcription factor PlcR, a positive regulator mainly of chromosomally encoded extracellular virulence factors that are important during mammalian and insect infections by B. cereus and B, thuringiensis ; and 3) being part of the genetically monomorphic B. anthracis cluster by phylogenetic analysis. 55 In addition, B. anthracis requires two large plasmids for full virulence: pXO1, which encodes the anthrax toxins, and pXO2, which encodes the protective poly-γ-D-glutamate capsule.…”
Section: Anthrax: a Case Study In Slow Integrationmentioning
confidence: 99%